PENGARUH PENYULUHAN MENGGUNAKAN AUDIO VISUAL TENTANG ASI EKSKLUSIF TERHADAP PENGETAHUAN DAN SIKAP IBU HAMIL DI PUSKESMAS SINGGANI KOTA PALU - Idris, Idris; Enggar, Enggar (Poltekkes Kemenkes Palu, 2019)
Breastfeeding is a physiological process to provide optimal nutrition for babies and one of the first steps for humans to have a healthy and prosperous life. The low coverage of exclusive breastfeeding is still a big problem for the State of Indonesia. There are several ways that can be done to increase exclusive breastfeeding, one of which is health education. The use of video as a means of education is now starting to be developed in line with current technological advances. The purpose of this study was to determine the effect of exclusive breastfeeding counseling with audio visual on the knowledge and attitudes of pregnant women in the work area of Singgani Health Center. This research is a pre-experimental study with the design of one group pretest-posttest. The number of samples is 33 respondents. The sampling technique uses purposive sampling. The analysis used in this study was the Wilcoxon test. The results of the univariate analysis of data on pretest knowledge with good categories were 24 people (72.7%) and the poor categories were 9 people (27.3%) Knowledge of posttest with good categories as many as 21 people (63.6%) were less than 12 people ( 36.4%). The pretest attitude in the good category was 16 people (48.4%), the poor category was 17 people (51.6%). The posttest attitude in the good category was 21 people (63.6%) in the poor category of 12 people (36.4%). The results of the bivariate analysis of the knowledge of the pretest posttest knowledge (P value 0.002 (<0.05). The posttest pretest attitude (P value 0.363 (> 0.05). The conclusion shows that there is the influence of exclusive breastfeeding counseling with video media on the knowledge of pregnant women in the Singgani Health. There is no effect of exclusive breastfeeding counseling with audio visual on the attitudes of pregnant women in the Singgani Health Center. The suggestion is that midwives are expected to further increase the use of increasingly developing technology, one of which is the use of audio visual to provide counseling. Keywords: Exclusive Breastfeeding, Audio Visual, Knowledge, Attitude,